Post-reform trends in wage inequality: the case of urban Bolivia - Susan Steiner; Julius Spatz (Kiel Institute for World Economics (IfW), 2002)
This paper seeks to contribute to the ongoing controversy on the distributional effects of structural reforms in developing countries. Applying inequality indices and Fields' (2001) decomposition methodology to Bolivian household survey data of the years 1989 to 1997, we identify recent trends in wage inequality of urban Bolivia. Using a rent-based dual-economy model, we can link these trends to the structural reforms undertaken in Bolivia since 1985.
Keywords: D31; J50; L16; O17; 330; Structural Reforms; Inequality; Dual Economy; Bolivia; Anpassungsprogramm des IWF; Wirtschaftsreform; Wirtschaftspolitische Wirkungsanalyse; Einkommensverteilung; Städtische Armut; Dualökonomie; Lohnstruktur; Rent Seeking; Schaetzung; Dekompositionsverfahren; Theorie; Bolivien